The design of a fuzzy logic system for control of an unmanned aircraft - Assuncao, J. M. V. (Cranfield University, 1996)
Many control problems are based on control objectives easily quantified and consequently realisable by standard control synthesis methods. When an unmanned aircraft navigates, it moves inside a complex environment due to interactions with its surrounding and time varying environmental conditions. Several causes of perturbations have been identified as for example gusts and corrupted information of position. The characteristics of possible missions carried out by the un manned aircraft leads to the desire to construct navigation control systems which when operated in perturbed environments combine the advantages of smooth control with accurate navigation. Rule based, and adaptive controllers have favourable properties for such systems. This thesis investigates the use of a rule based navigation controller for a particular unmanned aircraft, the XRAEl aircraft. To achieve this objective several different types of fuzzy logic controllers are analysed as for example conventional and direct and indirect adaptive fuzzy controllers. They are designed by employing simple control engineering knowledge and subsequently validated using a stability method. For this purpose diverse stability methods are described and a new technique presented, the fuzzy root locus method, which is also based on the introduction of a new concept for fuzzy logic controllers, the fuzzy cell. The realisation of this work has been achieved by a series of simulation tests employing different processes and a simulation model of the XRAEl aircraft. The conclusions drawn from the results of the experiments consider in general that a rule based controller can improve the quality of navigation when compared to conventional controllers.